Physiological Basis of Exercise Performance and Fatigue: Energy Systems and Metabolic Regulation - Suvankulovna, Pardaeva Zilola (American Journal of Biology and Natural Sciences, 2025)
This article explores the physiological and biochemical mechanisms that underpin human exercise performance and the onset of fatigue. It focuses on the dynamic interplay of energy systems—the phosphagen system, anaerobic glycolysis, and aerobic metabolism—and how they collectively sustain muscular work under varying intensities and durations of activity. The study also examines metabolic regulation involving ATP resynthesis, mitochondrial function, substrate utilization, and hormonal control, all of which determine endurance and power capacity. Particular attention is given to the molecular and systemic causes of fatigue, including energy depletion, acidosis, oxidative stress, and neuromuscular factors. The goal of this analysis is to provide an integrated understanding of how cellular energetics and metabolic adaptations influence performance and recovery, forming the foundation for optimizing training and athletic performance. This article provides a detailed examination of the physiological mechanisms that determine exercise performance and the onset of fatigue, with special emphasis on the regulation of energy systems and metabolic pathways. It analyzes how the human body converts chemical energy into mechanical work through interlinked bioenergetic processes that operate in a time-dependent and intensity-specific manner. The research highlights how the phosphagen, glycolytic, and oxidative systems cooperate to ensure continuous ATP resynthesis during muscular contraction. It also explores the cellular and systemic causes of fatigue, including substrate depletion, ionic imbalance, accumulation of metabolites, and impaired mitochondrial efficiency. The aim is to integrate molecular, cellular, and systemic perspectives to explain how energy metabolism adapts to physical stress and how these adaptations influence endurance, power, and recovery capacity.